Dampak Media Televisi Pada Perilaku Negatif Remaja (Studi Kasus Desa Gladagsari Kecamatan Ampel Kabupaten Boyolali tahun 2015) - PURWANTI, Dwi, Dra. Sundari, SH. M.Hum (2015)
This study aims to describe the intensity of teenagers watching television, the negative impact of television media and to find solutions to mitigate the impact of television media on adolescent negative behavior of teenagers in the village of Gladagsari the District Ampel, Boyolali 2015 District. This research method is a case study because it focuses on a particular case. Techniques of collecting data using interviews, observation, and documentation. The results showed that: 1) the majority of adolescents village districts Gladagsari Ampel Boyolali 2015 district has a high intensity watch without limitation of time, the intensity of watching television more than one hour per day, the choice of the form of soap opera teen favorite shows, and respondents were very focused attention to television without Other activities; 2) television can shape and influence adolescent behavior that highlight particular elements of violence, even leading to poenografi because basically they are in the stage of looking for identity; 3) Solutions taken to counteract the negative effects of television on adolescent behavior is negatively need to make arrangements for themselves about daily activities, should be able to sort out where the good and bad of a show or to emulate their idols. For relevant agencies to oversee the expected role and filter any content so that each television broadcast more wisely on character education and in accordance with the existing norms. Keyword: television media, negative behavior, teen